Society of Ethnomusicology - Rhodes, Willard (International Library of African Music, 1956)
In December, 1952, at the 51st Annual Meeting of the American Anthropological Association in Philadelphia, David P. McAllester, Alan P. Merriam, and the writer, met and decided to attempt to re-establish communication among scholars in the field of ethnomusicology. To this group was added Charles Seeger, at that time Director of Music and Art of the Pan-American Union, Washington, D.C. Seeger had been President of the American Society for Comparative Musicology before it became defunct in the late 1930’s, and was able to supply a sense of continuity with the past while contributing valuable advice in the development of a program of action.
Keywords: African Music